2003
DOI: 10.1375/bech.20.2.117.24839
|View full text |Cite
|
Sign up to set email alerts
|

Willingness, Confidence, and Knowledge to Work with Adolescent Sex Offenders: An Evaluation of Training Workshops

Abstract: Increasing attention is being paid to best practice in mental health sciences. One crucial aspect of this is the extent to which the mental health workforce has the knowledge and skills to implement state-of-the-art interventions. Recently, evidence has indicated that sexual offending often begins in adolescence, can be a persistent disorder when left untreated, and is associated with a range of other mental health problems in the perpetrator and subsequently in victims. A small number of evaluations of treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Capacity building efforts were focused specifically on the provision of formal training programs (see Dadds, Smallbone, Nisbet, & Dombrowski, 2003) and, particularly when collaborative partners were unable to attend training workshops due to their remote locations, on case consultation, professional supervision, opportunities to observe GYFS clinicians, and the provision of written resources.…”
Section: Improvements In Therapeutic Engagementmentioning
confidence: 99%
“…Capacity building efforts were focused specifically on the provision of formal training programs (see Dadds, Smallbone, Nisbet, & Dombrowski, 2003) and, particularly when collaborative partners were unable to attend training workshops due to their remote locations, on case consultation, professional supervision, opportunities to observe GYFS clinicians, and the provision of written resources.…”
Section: Improvements In Therapeutic Engagementmentioning
confidence: 99%
“…''; and ''At present, how willing are you to work with adolescents who sexually offend?''. Dadds et al (2003) reported a Cronbach's alpha of .84 for the eight-item scale, indicating good scale reliability. Dadds et al also reported that scores varied according to the qualifications and experience of trainees, indicating external validity.…”
Section: Methodsmentioning
confidence: 99%
“…The GYFS Collaborative Partner Questionnaire (GCPQ) was used to survey participants. The GCPQ consists of the GYFS (formerly GAFATC) Skills Questionnaire (GSQ) (Dadds et al, 2003), together with additional items assessing obstacles and benefits associated with the collaborative model. The GSQ was originally designed for the purposes of evaluating GYFS training outcomes, and specifically to assess professional workers' self-rated knowledge, skills, and confidence to work with youth who have committed sexual offences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment efficacy relies not only upon empirically validated models of best practice, but is also influenced by the availability of professionals with the knowledge, specialist skills and willingness to implement those models (Dadds, Smallbone, Nisbet & Dombrowski, 2003). In contrast to the abundant data on the assessment and treatment of sexual offenders, research investigating the impact of treating this population on clinicians is significantly one-sided.…”
Section: Introductionmentioning
confidence: 99%